2010
DOI: 10.1097/ccm.0b013e3181f859a6
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after convulsive status epilepticus

Abstract: Ninety days after intensive care unit admission for convulsive status epilepticus, half the survivors had severe functional impairments. Longer seizure duration, cerebral insult, and refractory convulsive status epilepticus were strongly associated with poor outcomes, suggesting a role for early neuroprotective strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 45 publications
8
109
1
4
Order By: Relevance
“…In 21 studies including adults, definitions were more variable, including 30‐minute seizure duration limits,7, 8, 9, 10, 11, 12, 13 and 5‐minute clinical seizure duration or more than two seizures without return to baseline between seizures 14, 15, 16, 17, 18, 19. One study also chose a 10‐minute clinical seizure duration cutoff limit 20. Two studies reported patients with prolonged refractory SE, including patients with SE that persists or recurs over a period of ≥7 days after the initiation of continuous general anesthesia 21, 22.…”
Section: Definitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 21 studies including adults, definitions were more variable, including 30‐minute seizure duration limits,7, 8, 9, 10, 11, 12, 13 and 5‐minute clinical seizure duration or more than two seizures without return to baseline between seizures 14, 15, 16, 17, 18, 19. One study also chose a 10‐minute clinical seizure duration cutoff limit 20. Two studies reported patients with prolonged refractory SE, including patients with SE that persists or recurs over a period of ≥7 days after the initiation of continuous general anesthesia 21, 22.…”
Section: Definitionsmentioning
confidence: 99%
“…In mixed populations of adults and children, subsequent epilepsy after SE may occur in 22%‐41%,14, 30 which is less than in patients with history of RSE, who have a 87.5% risk of subsequent epilepsy 14. Only one adult study showed that 31% of patients have subsequent epilepsy or worsening of previous epilepsy after SE 20. The main predictor of subsequent epilepsy is the underlying SE etiology, and nonfebrile‐nonidiopathic,28 remote symptomatic,29 structural, and acute symptomatic (eg, anoxic brain injury)30 etiologies are usually associated with higher risk.…”
Section: Long‐term Outcomes Of Sementioning
confidence: 99%
See 3 more Smart Citations